Campi Flegrei and the Metropolitan Area of Naples. Emergency planning in a high-risk territory - Giuseppe Mazzeo (TeMA: Journal of Land Use, Mobility and Environment)
The territory surrounding the city of Naples is characterized by three active volcanic risk sources: Vesuvius, Campi Flegrei, and the island of Ischia. The objective of this study is to examine the characteristics of emergency planning in response to volcanic risk. The methodology of the paper consists of three steps. The first step identifies the fundamental elements of this type of planning using international studies and national frameworks. The second step analyzes the emergency plan for Campi Flegrei, focusing particularly on its primary objective: the evacuation of the population in the event of a volcanic eruption. Additionally, this section examines the recent worsening of bradyseism in the Pozzuoli area, which, due to its location, has increased experts’ attention on the entire Campi Flegrei region. The third step involves a coherence analysis between the contents of the Campi Flegrei emergency plan and the guidelines outlined in the international studies and national frameworks introduced in the first step. The main results of the analysis highlight the strengths and weaknesses of the plan. Another significant finding confirms the close relationship between emergency planning and territorial planning. The current situation of the metropolitan area of Naples has been influenced by territorial plans that have paid insufficient attention to the risks present in the region. The next steps of the research emphasize the necessity for the new metropolitan plan to serve as an active tool for addressing territorial vulnerabilities. This should be approached with a focus on integrating risk mitigation into broader spatial planning initiatives.